2019
DOI: 10.1002/nau.24104
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcome and symptom improvement in patients with interstitial cystitis/bladder pain syndrome with or without regular follow‐up and treatment

Abstract: Aims: Interstitial cystitis/bladder pain syndrome (IC/BPS) is a chronic disease, which is difficult to treat. Patients usually seek for new therapies and might not follow-up regularly. This study investigated long-term symptom changes in patients with IC/BPS, especially in those who were lost to follow-up. Methods: We enrolled patients with IC/BPS with a history of >5 years and having comprehensive medical records, baseline IC symptom index and IC problem index, O'Leary-Sant symptom score, and visual analog sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…[14][15][16] However, it is unknown whether the Centering model would be beneficial in ICBPS treatment. Because current ICBPS treatments have limited efficacy and poor adherence, 7,17 there is an urgent need for care models that optimize patient engagement.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16] However, it is unknown whether the Centering model would be beneficial in ICBPS treatment. Because current ICBPS treatments have limited efficacy and poor adherence, 7,17 there is an urgent need for care models that optimize patient engagement.…”
mentioning
confidence: 99%
“…Interstitial cystitis/bladder pain syndrome (ICBPS) affects up to 10% of women 1,2 and causes stigma and shame, 3,4 compromising patients’ ability to voice their needs. Furthermore, few treatments for ICBPS are widely effective, 5,6 and less than half of patients improve with treatment 7,8 . Women with ICBPS have expressed that novel treatments appeal to them, 6,9 and they also want physicians to address the psychosocial aspects of this disease 3 …”
mentioning
confidence: 99%
“…Because the pathogenesis of IC/BPS is not well-understood, it is rare for complete resolution of IC/BPS to occur after a single treatment [1]. Currently, most treatments for IC/BPS mainly target symptomatic relief, rather than resolution of disease; however, even satisfactory improvement of symptoms may not be achieved in all patients [49]. Researchers have used BoNT-A for treatment of patients with IC/BPS in clinical trials since 2004, and the initial results of various studies showed promising outcomes [50,51].…”
Section: Resultsmentioning
confidence: 99%
“…Transparency and honesty with the patient about this from the outset are recommended to manage and set realistic expectations. Yeh et al recorded outcomes of BPS patients at long-term follow-up (mean duration 16.6 ± 9.75 years) [ 12 ]. Only 12% achieved a status of being symptom-free, and 47% reported an improvement of at least 50% compared with the baseline.…”
Section: Methodsmentioning
confidence: 99%